2011
DOI: 10.1002/srin.201000036
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behaviour and Microstructural Evolution During Hot Compression of AISI 904L

Abstract: The hot deformation behaviour and microstructural evolution of AISI 904L super‐austenitic steel has been investigated by means of hot compression tests. The tests were carried out on a Gleeble 1500D thermo‐mechanical simulator in the temperature range from 850 °C to 1150 °C and at strain rates range from 0.001 s−1 to 5 s−1. The microstructure evolution was examined by means of light optical microscopy (LOM). The results show that after an initial deformation hardening, softening mechanisms occur. The peak stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…This signifies that the deformation mechanism is dominated by the DRX instead of diffusion or DRV. Combining with other austenitic stainless steels, such as 301, 304, 316, 317, and 904L steels [3,10,32,33], as shown in Fig. 4, there is no doubt that the Q value for hot deformation of as-cast 254SMO SASS is significantly high, indicating that the hot deformation for this alloy is rather difficult.…”
Section: Activation Energy and Constitutive Equationmentioning
confidence: 92%
See 2 more Smart Citations
“…This signifies that the deformation mechanism is dominated by the DRX instead of diffusion or DRV. Combining with other austenitic stainless steels, such as 301, 304, 316, 317, and 904L steels [3,10,32,33], as shown in Fig. 4, there is no doubt that the Q value for hot deformation of as-cast 254SMO SASS is significantly high, indicating that the hot deformation for this alloy is rather difficult.…”
Section: Activation Energy and Constitutive Equationmentioning
confidence: 92%
“…[8]) and the acceleration of recovery process [9]. Thus, the sluggish DRX could be observed in the SASSs [3,10]. In order to reveal the distinct hot workability for this class of materials, the investigation on the correlation between processing variables (temperature, T, strain rate, _ e, and strain, e are included) and microstructural evolution in the hot working becomes particularly significant.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additions of these elements impart a remarkable improvement in oxidation resistance, microstructural stability and high temperature strength at elevated temperatures. Therefore, SASSs have been widely used as important structural materials for application in engineering fields such as chemical, petrochemical, oceanic, nuclear industries and so on in recent decades [1][2][3][4]6,7], it can be said that SASS applications successfully provide a bridge between cheap austenitic stainless steels and relatively expensive special superalloys [8].…”
Section: Introductionmentioning
confidence: 99%
“…As observed in past studies, a significant positive correlation of Cr, Ni and Mo elements has been found with the SFE in austenitic grades of stainless steels (e.g., 34 mJ· m −2 of AISI 305, 78 mJ· m −2 of AISI 316, 94 mJ· m −2 of AISI 310S and 164 mJ· m −2 of AISI 904L) [9,11]. Along with the increase in the SFE, steels are very susceptible to hot cracking during hot deformation, especially edge cracking due to the sluggishness of the dynamic recrystallization process (DRX) [7,12].…”
Section: Introductionmentioning
confidence: 99%